Development of multigrain snack bar with tempeh flour and spirulina for adolescent nutrition - Nur Khoiriyah; Liliek Pratiwi; Muhammad Zakaria; Lahana Deling (AcTion: Aceh Nutrition Journal, 2026)
The prevalence of adolescent malnutrition in Indonesia is still high, namely stunting (23,7-24,1%), overweight/obesity (12,1-16,2%), and anemia (16,2%). One contributing factor is the consumption of unhealthy foods. This study aimed to develop a multigrain snack bar by adding tempeh flour and Spirulina, which provide protein, iron, and fiber, to prevent malnutrition. This study was conducted from March to May 2025 using a completely randomized design with tempeh flour and spirulina powder proportions of 95:5 (F1), 90:10 (F2), and 85:15 (F3). The product formulation was performed at the Nutrition Laboratory of Universitas Muhammadiyah Cirebon, Cirebon. The analysis included organoleptic (30 panelists), nutritional content, formula selection, and nutritional contribution analyses. Data were analyzed using ANOVA with Duncan’s test. There were significant differences in color, aroma, taste, overall, ash, fat, protein, carbohydrate, and iron content among the formulations (p<0.05). F1 was the optimal formulation, with 17,63% protein, 3,24 mg/100 g iron, and 3,86% fiber. One serving (20 g) contributed 4-5% of the energy requirement for adolescents (13-18 years). In conclusion, F1 was the most preferred and provided essential nutrients to meet the needs of adolescents. This study is novel in that it develops a product from tempeh and Spirulina as a potential innovative solution to address nutritional problems in adolescents.